ChemInform Abstract: Enzyme‐Catalyzed Regio‐ and Enantioselective Preparative Scale Synthesis of (S)‐2‐Hydroxy Alkanones. Issue 36 (September 2015) - Loderer, C.; Ansorge‐Schumacher, M. B.
Abstract α‐Hydroxy alkanones ((S)‐II) are obtained by stereoselective enzyme‐catalyzed diketone reduction with high enantiomeric purity.